Synthesis and Photocatalytic Efficiency of Sunlight Driven Novel Ternary Metal Oxide Nanophotocatalyst - Ullah, Inam; Ali, Shaukat; Asif Hanif, Muhammad; Anjum Zia, Muhammad (Asian Journal of Chemistry, 2015)
Effluents from the textile industry usually contain high concentrations of organics and are characterized by deep colour as well as high in chemical oxygen demand and total organic carbon values. Dyes from dyeing operations are the major source of colour in textile effluents. Currently many physical and chemical techniques are available for treatment but these are costly and have disposal problem at industrial level. In the present study co-precipitation method was used to prepare sunlight driven efficient nanophotocatalyst aluminium zinc ferrite (Al1-xZnxFe2O4). It was characterized for its structural properties by X-ray diffraction, scanning electron microcopy, energy dispersive X-ray analysis (EDX). The photocatalytic activity was evaluated by degrading reactive black B dye under sunlight irradiation with the help of UV-visible spectrophotometer. The observed photo degradation rate was 91 % in 120 min. Aluminium zinc ferrite photocatalyst was separated from reaction mixture and recycled for 7 cycles of reuse without appreciable loss of activity.